2019
DOI: 10.31234/osf.io/b7kh8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Associations between drinking and cortical thickness in young adult drinkers: Findings from the Human Connectome Project

Abstract: Background. Previous neuroimaging studies examining relations between alcohol misuse and cortical thickness have revealed that increased drinking quantity and alcohol use disorder severity are associated with thinner cortex. Although conflicting regional effects are often observed, associations are generally localized to frontal regions (e.g., dorsolateral prefrontal cortex (DLPFC), inferior frontal gyrus (IFG), and anterior cingulate cortex), with parietal and temporal cortex also implicated in some studies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Additionally, previous research has shown increased ventral striatal volume in binge drinkers (common amongst college students) compared to healthy controls but decreased volume in individuals with AUD (Howell et al, 2013). Other reported changes include reduced prefrontal gray matter volume, (Luciana et al, 2013, Yang et al, 2016, Meda et al, 2017 and greater than expected decreases in cortical thickness in adolescents and young adults using alcohol (Luciana et al, 2013, Pennington et al, 2015, Morris et al, 2019, indicating alterations in natural developmental changes that occur in adolescence and young adulthood in those who consume alcohol. Finally, significantly smaller amygdala volume has been seen in alcohol-naïve individuals with a parent who developed AUD by age twenty-five with at least two more first-degree relatives with AUD (Benegal et al, 2007).…”
Section: Introductionmentioning
confidence: 95%
“…Additionally, previous research has shown increased ventral striatal volume in binge drinkers (common amongst college students) compared to healthy controls but decreased volume in individuals with AUD (Howell et al, 2013). Other reported changes include reduced prefrontal gray matter volume, (Luciana et al, 2013, Yang et al, 2016, Meda et al, 2017 and greater than expected decreases in cortical thickness in adolescents and young adults using alcohol (Luciana et al, 2013, Pennington et al, 2015, Morris et al, 2019, indicating alterations in natural developmental changes that occur in adolescence and young adulthood in those who consume alcohol. Finally, significantly smaller amygdala volume has been seen in alcohol-naïve individuals with a parent who developed AUD by age twenty-five with at least two more first-degree relatives with AUD (Benegal et al, 2007).…”
Section: Introductionmentioning
confidence: 95%
“…In young adults, associations between reduced cortical thickness in frontal regions (e.g., dlPFC, ACC, orbitofrontal cortex [OFC]) and drinking were driven by men; an effect not observed in women (Morris et al, 2019). In a longitudinal cohort study of over 30 years, moderate-to-high alcohol consumption was also associated with greater hippocampal shrinkage in men compared to women (Topiwala et al, 2017).…”
Section: Brain Volumementioning
confidence: 99%